Consumer Actions Toward Unfulfilled Peace Agreement by Business Actor (A Case Study of Insurance Disputes in the BPSK of Banjarmasin City) - Wafix Azijah; Amelia Rahmaniah; Tuti Hasanah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Mediation dominates the dispute resolution process in BPSK Banjarmasin, including insurance disputes between consumers (TMC) and insurance business actors, resulting in a Peace Agreement. However, in reality, the business actors do not implement the Peace Agreement. The aim of this research is to identify the actions and factors causing consumer actions regarding the non-implementation of the Peace Agreement by the business actors in the dispute. This study adopts an empirical legal research method and utilizes a case study approach. The collected data is then processed and analyzed descriptively and qualitatively. The result of the research indicate that the action taken by the consumer is to negotiate with the business actors by contacting them through WhatsApp and Telegram. Several actions that should have been taken by the consumer but were not: 1) The consumer did not register the Peace Agreement resulting from the mediation by filing a lawsuit in court; 2) The consumer did not resolve the dispute through arbitration; 3) The consumer did not file a breach of contract lawsuit regarding the Peace Agreement resulting from the mediation that the business actors did not fulfill. There are three factors causing consumer actions, namely: 1) Knowledge; 2) Economic; 3) Cultural.